Web‐based chlamydia education for university students: A pilot project - Nancy G. Russell; Phyllis W. Sharps; Elizabeth Sloand (Wiley, 2022)
Abstract Aims Chlamydia disproportionately affects individuals aged 15-24 years. A lack of chlamydia knowledge in this high‐risk group likely contributes to decreased testing, but interventions to increase chlamydia knowledge in this population are not well‐described in the literature. The purpose of this pilot project was to increase chlamydia knowledge in a sample of university students using nurse‐developed web‐based education. Design A pre‐ and post‐test design was used to evaluate participant knowledge of chlamydia before and after completing a nurse‐developed web‐based education intervention designed for university students. Methods Forty‐seven undergraduate students at one U.S. university participated. A focus group and scientific evidence informed the development of the web‐based education. Results Participants had a significant increase in chlamydia knowledge after completing the online educational intervention (M = 8.0, SD = 0.000) compared to baseline (M = 6.5, SD = 1.5), t(33) = −5.821, p < .0001. Pilot results provide promising evidence that web‐based nurse‐developed education designed specifically for university students can increase chlamydia knowledge.